Review: Effect of Red Cabbage Juice (Brassica oleracea var. Capitata f. Rubra) on SGPT Level - Hesty Wahyuningsih; Andina Putri Aulia (Borneo Journal of Medical Laboratory Technology, 2020)
Red cabbage (Brassica oleracea var. Capitata f. Rubra) is a vegetable widely used in Indonesian cuisine. Red cabbage is rich in anthocyanins to reduce SGPT levels in drug-induced liver injury (DILI). This study aims to determine the effect of red cabbage juice on SGPT levels in acetaminophen-induced liver injury. In this post-test, only the control group study, male Wistar rats (300g), were randomly divided into 5 groups (K1-K2-K3-K4-K5). Acetaminophen was given to induce liver injury in rats. The rats were treated with the cabbage juice (at the dose of 0.5g/ml or 0.7g/ml or 0.9g/ ml. Data were analyzed using One way ANOVA and LSD post hoc test. Mean SGPT levels for K1, K2, K3, K4, K5 was 58.43 ± 7.18 UI / L, 71.20 ± 9.13 UI/L, 55.73 ± 9.51 UI / L, 72.80 ± 3.47 UI /L, 72.63 ± 3.01 UI /L, respectively. One way ANOVA resulted in p=0.00 (p <0.05). The post hoc LSD test showed significant differences (P <0.05) between all groups except between groups K1-K3, K2-K4, and K2-K5 (p> 0.05). Red cabbage juice can reduce SGPT in acetaminophen-induced liver injury in rats. The most effective dose was 0.5 g/ml.